PENGARUH PEMBERIAN DOSIS VAKSIN AVIAN INFLUENZA INAKTIF PADA ITIK JANTAN TERHADAP JUMLAH SEL DARAH PUTIH DAN TITER ANTIBODI YANG DIHASILKAN - Eva Yulistiya; Purnama Edy Santosa; Sri Suharyati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The aim of research to knowing the effect of inactived AI (Avian Influenza) vaccine doses to white blood cells and titer of antibodies also to knowing the most well vaccine doses to white blood cells and titer of antibodies production, already implemented in December 2015 in Sabah Balau, Tanjung Bintang District, South Lampung, with the amount of duck used were 54 tail a male. Method of this research was Completely Randomized Design consisting of 6 treatment (P0: control with distilled water provission, P1= administration of inactivated AI vaccine of 0,1 ml; P2= of inactivated AI vaccine doses of 0,2 ml; P3= of inactivated AI vaccine doses of 0,3 ml; P4= of inactivated AI vaccine doses of 0,4 ml; P5=of inactivated AI vaccine doses of 0,5 ml) with repeat 3 times. The result of analysis of variance showed that the level inactived AI vaccine againts white blood cells (P0= 52,63; P1= 69,78; P2= 69,10; P3= 58,82; P4= 73,83 and P5= 69,10) and antibody titer (P0= 4,06; P1= 3,67; P2= 5,33; P3= 5,00; P4= 3,67 and P5= 4,70) at 5 days old male ducks no significant (p>0.05) because white blood cells are produced every duck is more influenced by maintenance was not good and the sampling process so the duck become stressful and effects the amount of white blood cells in the body. Antibody titer not effect because sampling process is too short when sampling process are longer excepted to show different levels of antibody titers at each doses. Keywords : Antibody Titer, Avian Influenza, Male Ducks, Vaccine Doses, White Blood Cells